2022
DOI: 10.3390/sym14071373
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Seismic Design of Hybrid Isolation Systems with Gap-Tunable BRBs for Bearing-Supported Bridges

Abstract: This study proposes a class of hybrid isolation systems constructed by combining Buckling Restrained Braces (BRBs) with Rubber Bearings (RBs) or Lead Rubber Bearings (LRBs) for mitigating the seismic responses in bearing-supported bridges under strong earthquakes. Firstly, two different hybrid isolation systems (RB–BRB and LRB–BRB) were preliminarily designed based on the energy-conservation concept in the case of a bridge with Y-shaped piers, which can meet all the energy demands at different seismic hazard l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The system could improve the energy dissipation capacity of the BRB and keep the RC bridge bents elastic. Liu et al [ 97 ] proposed two different hybrid isolation systems (RB (Rubber Bearing)–BRB and LRB (Lead Rubber Bearing)–BRB) on bridge piers. Based on the nonlinear time history, results demonstrated that the LRB–BRB was the most effective isolation system.…”
Section: Damping Effect Of Brbmentioning
confidence: 99%
“…The system could improve the energy dissipation capacity of the BRB and keep the RC bridge bents elastic. Liu et al [ 97 ] proposed two different hybrid isolation systems (RB (Rubber Bearing)–BRB and LRB (Lead Rubber Bearing)–BRB) on bridge piers. Based on the nonlinear time history, results demonstrated that the LRB–BRB was the most effective isolation system.…”
Section: Damping Effect Of Brbmentioning
confidence: 99%
“…Cao et al proposed a lead rubber isolation bearing for multi-stage composite bridges that meets specific performance under different levels of seismic hazards to ensure isolation efficiency and limit the ability of bearings to move too much under different seismic effects. Research has shown that this bearing has high isolation efficiency for small and medium-sized earthquakes and can effectively limit the displacement of the bridge [6].In order to meet the application of isolation bearings in different structures and situations, researchers conducted a combination study on isolation bearings.Liu et al prepared a hybrid isolation system that combines buckling restrained support (brb) with rubber bearings (RBs) or lead rubber bearings (LRBs) to meet all energy requirements under different seismic hazard levels, significantly improving the seismic performance of the bridge; Reduce seismic response under different earthquake scenarios [7].Peng et al combined rubber isolation bearings, pure tension supports, and ductile bridge piers to improve the seismic performance of isolation bearings, meet the very rare seismic requirements of vrgm, and reduce the seismic response of the structure [8].Researchers conducted a series of shaking table tests to demonstrate that rubber isolation bearings have excellent isolation effects [9][10][11].Rubber bearings have disadvantages such as low damping and large horizontal structural displacement, which affect the normal operation of buildings.Therefore, the emergence of friction pendulum sliding bearings has achieved more perfect earthquake control.Chen et al conducted research on the seismic performance of bridges using an isolation scheme combining friction pendulum bearings and friction pendulum bearings with viscous dampers. The results showed that both friction pendulum bearings (FPB) and shock absorption and isolation combinations (CSDI) have good seismic absorption and isolation effects [12][13][14].Jamalvandi et al studied single friction pendulum (SFP) bearings and triple friction pendulum (TFP) bearings, which are completely passive isolation devices with low sensitivity, high stability, and strong self-limiting recovery ability within the frequency range of seismic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [3] studied a class of hybrid isolation systems constructed by combining Buckling Restrained Braces (BRBs) with Rubber Bearings (RBs) or Lead Rubber Bearings (LRBs) for mitigating the seismic responses in bearing-supported bridges during strong earthquakes. Firstly, two different hybrid isolation systems (RB-BRB and LRB-BRB) were preliminarily designed based on the energy conservation concept in the case of a bridge with Y-shaped piers, which can meet all the energy demands at different seismic hazard levels.…”
Section: Introductionmentioning
confidence: 99%